An improved LB method for predicting dynamic characteristics of Vertical Axis Wind Turbine airfoils. Issue 4 (August 2022) - Li, Shoutu; Wang, Qing; Yang, Congxin
One of the important challenges for Vertical Axis Wind Turbine (VAWT) is to fully understand its dynamic characteristics in different operating conditions. Meanwhile, it is necessary to seek a fast and accurate method to evaluate the dynamic characteristic of VAWT. In this study, we improve the LB model by considering the operating principle of VAWT to study the dynamic characteristics of the dedicated and commonly used VAWT airfoils in different operating conditions. The results show that the improved LB model is suitable for simulating the dynamic characteristic of VAWT with a thick airfoil. Although the asymmetric airfoil shows the higher lift coefficient, their dynamic characteristic appears huge fluctuation as the increases of tip speed ratio. Moreover, at a low tip speed ratio, the advantages of the asymmetric airfoil are not obvious. While the dynamic characteristic of the symmetric airfoil is relatively stable with the variation of tip speed ratio.